Struktur Semantis Verba Kiru ‘Potong’: Kajian Metabahasa Semantik Alami - Dewi, Sifta Sari; Mulyadi, Mulyadi; Pujiono, Mhd (IZUMI, 2019)
(Title: Semantic Structures Of Kiru ‘Cut’ Verbs) This study aims to analyze the categorization and meaning of the kiru "cut" verbs by Natural Semantic Metalangue theory.This research uses a qualitative approach. The categorization and meaning are analyzed by the Natural Semantic Metalangue Theory. Data collection is done by competent methods. Data analysis uses the identity and distributional methods. The presentation of data results is done by formal and informal methods. There are 21 kiru ‘cut’ verbs. The results showed that the kiru ‘cut’ verbs consisted of two categories seen from the Indonesian and Japanese semantic prime table, namely 1) 'X does something to someone’ divided into two subcategories, namely 1.1) 'X does something to someone with something’ and 1.2)'X does something on someone in a certain time' and 2) 'X doing something on something’ is divided into two subcategories, namely 2.1)'X does something on something with something’ and 2.2) 'X does something on something in a certain time'. Furthermore, the meaning of the kiru ‘cut’ verbs are formed by the original meaning of doing (suru) and happening (okoru/okiru) which combine to form the syntax of universal meaning ‘X do something on Y, something happens to Y’.   gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor